Early and midterm results of thoracic endovascular aortic repair using a branched endograft for aortic arch pathologies: A retrospective single-center studyCentral MessagePerspective - Tomoaki Kudo, MD, PhD; Toru Kuratani, MD, PhD; Kazuo Shimamura, MD, PhD; Yoshiki Sawa, MD, PhD (JTCVS Techniques)
Background: Zone 0 landing hybrid thoracic endovascular aortic repair (TEVAR) includes a few moderately invasive surgical procedures. To reduce invasiveness, TEVAR with a branched aortic arch stent-graft can be considered. This study aimed to elucidate the effectiveness of performing TEVAR using a Bolton (Bolton Medical, Inc, Sunrise, Fla) branched endograft by analyzing early and midterm results. Methods: We enrolled 28 patients (mean age, 78.4 years) who underwent TEVAR with the Bolton branched endograft in Osaka University Hospital between October 2012 and June 2018 with a mean follow-up period of 4.0 years. Double-side and single-side branched devices were used in 24 (85.7%) and 4 (14.3%) patients, respectively. Results: All procedures were successful; no cases of endoleak or conversion to open repair were noted during the 30-day postoperative period. The perioperative stroke rate was 14.3% (4 out of 28); midterm stroke was not detected. All patients with perioperative stroke had atheroma grade ≥2 in the brachiocephalic artery. No type 1a endoleak was reported during the early or midterm results. The cumulative survival rate, aorta-related death-free rate, and aortic event-free survival rate at 5 years were 80.8%, 95.8%, and 81.6%, respectively. Conclusions: We achieved satisfactory early and midterm results by using a Bolton branched endograft for high-risk patients with arch pathologies except for high postoperative stroke. Although this treatment method is associated with postoperative stroke, performing strict evaluation of atheroma may prevent such complication. By preventing intraoperative stroke, TEVAR with this custom-made Bolton branched endograft may be considered a less-invasive treatment.